Evaluation of the brain stem auditory evoked potential response among new borns post-recovery after hyper-bilirubinemia: An original research - Kunzes Dolma; Jathin Sam Thekkethil; Anish G Paul; P Srinivas Narasinga Rao; Taral Parikh; Vinej Somaraj (Wolters Kluwer Medknow Publications, 2023)
Introduction: Neurological harm from neonatal hyperbilirubinemia includes loss of hearing and encephalopathy. The current research used the "Brainstem Evoked Response Audiometry (BERA)" test to screen for as well as assess hearing loss in newborns who had recovered from hyperbilirubinemia. Materials and Procedures: A cross-sectional comparative investigation was conducted at a tertiary care center. Fifty neonates were included out of which 25 were healthy and 25 received treatment for the increased bilirubin. Prior to BERA testing, the subjects' ears were examined for any obstruction. Following a conventional lab procedure described, the BERA recordings were carried out after the neonate fell asleep on its own. The data collected were compared for the significance using the ANOVA, keeping P < 0.05 as significant. Results: In comparison to the controls, a large proportion of neonates in cases had BERA wave latencies that were delayed (I-R = 80, L = 84; III- R = 76, L = 84; V- R = 84, L = 88 percentages latencies). The percentage of subjects in whom the latencies was noted for the healthy neonates was lesser than the case group (I-R = 8, L = 24; III- R = 8, L = 8; V- R = 4, L = 12 percentages latencies). Comparable numbers of infants in each group had inter-peak latencies that were lengthy. Subjects in the case group showed that the threshold hearing as per the WHO grade was mild (R = 32, L = 36) and moderate (R = 32, L = 28). Conclusion: Elevated serum bilirubin may cause damage to hearing capability. After hyperbilirubinemia has been completely treated, BERA can detect even the slightest degree of hearing damage. BERA is therefore a useful technique for the quick recognition of hearing impairment in newborns. Early treatment helps in the prognosis so that the neurosensory systems can fully mature, and the patient can lead a quality life.